Three-dimensional modeling of geocell-reinforced straight and curved ballast embankments. (October 2018) - Liu, Yang; Deng, An; Jaksa, Mark
Abstract: This paper outlines a three-dimensional modeling study conducted on straight and curved geocell-reinforced embankments. The study uses the discrete element method to represent varying angularities of ballast infill and models their mechanical response under monotonic and cyclic loading conditions. The simulation results show good agreement with test results and the case studies indicate that the geocell enhances embankment stiffness under monotonic loading and improves its resilience when subjected to cyclic loading. The geocell more evenly distributes stresses within the ballast embankments. The reinforced ballast embankments also exhibit less vertical displacement and lateral spreading than the unreinforced ballast embankments do.